'Recognized, Valued and Supported'? The Experiences of Adult Siblings of People with Autism Plus Learning Disability. Issue 4 (5th March 2015) - Tozer, Rosemary; Atkin, Karl
<x xml:space="preserve">Abstract</x> Background The potential of adult siblings to offer long‐term support to a brother or sister with autism is rarely realized. To understand this, our study explores the expectations of social care among adult siblings. Method Using qualitative interviews, we spoke to 21 adult siblings about their family relationships and engagement with service delivery, met with 12 of their siblings with autism and talked to 12 social care staff. Results Siblings, although reflecting on the difficulties of growing up with someone who had autism, expressed a commitment towards their brother or sister. Most wanted involvement in their care. While some siblings described positive relationships with services, many felt marginalized. Practitioners largely confirmed their perceptions, while offering a justification for why they struggled to engage with adult siblings. Conclusion By understanding the way relationships between siblings change over time, adult siblings' contribution to the lives of their disabled brother or sister can be better supported.